Bacterial Meningitis in HIV-Infected Patients: Case Reports and Review of the Literature - Robert Tommasini; Ignatius W Fong (Canadian Journal of Infectious Diseases)
Meningitis is not an uncommon complication of the acquired immune deficiency syndrome. Purulent meningitis is not a well recognized infection in human immunodeficiency virus (HIV) positive patients. Three cases of bacterial meningitis caused by Streptococcus pneumoniae, Neisseria meningitidis and Listeria monocytogenes are presented. These cases illustrate that common community organisms may present in HIV positive patients. An acquired B cell defect may predispose to bacterial infections responsible for meningitis in HIV-infected patients.